Efektifitas Limbah Kulit Udang dalam Menurunkan CO dari Kendaraan Bermotor - Asma’ul Nur Aini; Ida Munfarida; Dyah Ratri Nurmaningsih (Fakultas Teknik, 2023)
Shrimp shell waste has not been widely used as an air pollutant adsorbent, most of the previous studies using chitosan adsorbent were not extracted from shrimp shell waste but from the fabrics chitosan powder directly. Therefore, this research combines the use of shrimp shell waste as an adsorbent to reduce CO levels from motorized vehicles. This study uses the observation method, namely direct research on the source of CO pollutants, especially motor vehicles. Tests on motorized vehicles took place with time variations of 10, 30, 50 minutes with variations in the mass ratio of chitosan of 1: 1 gram, 1: 2 gram, and 1: 3 gram. Extraction of shrimp shells into chitosan using deproteination, demineralization and deacetylation processes. In additon, the results of shrimp shell extraction in the form of chitosan were analyzed using Fourier Transform Infra-Red spectroscopy to determine the degree of deacetylation of chitosan. Furthermore, chitosan is used to reduce carbon monoxide levels from motorized vehicles by being glued to a test kit that has been made then plugged into the exhaust of a motorized vehicle and tested using a CO Analyzer. The results of the effectiveness test showed that the highest value was located in the 30-minute time variation, with the highest effectiveness value obtained at the 20th minute with a variation in the mass ratio of 1: 3 grams, which was 61.5%.